WACK!: art and the feminist revolution - Butler, Cornelia H.; Mark, Lisa Gabrielle; Museum of Contemporary Art (Los Angeles, Calif); Butler, Cornelia H.; Mark, Lisa Gabrielle; Museum of Contemporary Art (Los Angeles, Calif) (Museum of Contemporary Art, 2007)
Groundbreaking art from a revolutionary era, featuring work by more than 120 international artists, from Louise Bourgeois and Yoko Ono to Martha Rosler, Marina Abramović, and Cindy Sherman. There had never been art like the art produced by women artists in the 1970s, and there has never been a book with the ambition and scope of this one about that groundbreaking era. WACK! documents and illustrates the impact of the feminist revolution on art made between 1965 and 1980, featuring pioneering and influential works by artists who came of age during that period, Chantal Akerman, Lynda Benglis, Theresa Hak Kyung Cha, Valie Export, Mary Heilmann, Sanja Iveković, Ana Mendieta, Annette Messager, and others, as well as important works made in those years by artists whose careers were already well established, including Louise Bourgeois, Judy Chicago, Sheila Levrant de Bretteville, Lucy Lippard, Alice Neel, and Yoko Ono. The art surveyed in WACK! includes work by more than 120 artists, in all media, from painting and sculpture to photography, film, installation, and video, arranged not by chronology but by theme: Abstraction, "Autophotography," Body as Medium, Family Stories, Gender Performance, Knowledge as Power, Making Art History, and others. WACK!, which accompanies the first international museum exhibition to showcase feminist art from this revolutionary era, contains more than 400 color images. Highlights include the figurative paintings of Joan Semmel; the performance and film collaborations of Sally Potter and Rose English; the untitled film stills of Cindy Sherman; and the large-scale, craft-based sculptures of Magdalena Abakanowicz. Written entries on each artist offer key biographical and descriptive information and accompanying essays by leading critics, art historians, and scholars offer new perspectives on feminist art practice. The topics, including the relationship between American and European feminism, feminism and New York abstraction, and mapping a global feminism, provide a broad social context for the artworks themselves. WACK! is both a definitive visual record and a long-awaited history of one of the most important artistic movements of the twentieth century. Essays by: Cornelia Butler, Judith Russi Kirshner, Catherine Lord, Marsha Meskimmon, Richard Meyer, Helen Molesworth, Peggy Phelan, Nelly Richard, Valerie Smith, Abigail Solomon-Godeau, Jenni Sorkin Artists include: Marina Abramović, Chantal Akerman, Lynda Benglis, Dara Birnbaum, Louise Bourgeois, Judy Chicago, Lygia Clark, Jay DeFeo, Mary Beth Edelson, Valie Export, Barbara Hammer, Susan Hiller, Joan Jonas, Mary Kelly, Maria Lassnig, Linda Montano, Alice Neel, Senga Nengudi, Lorraine O'Grady, Pauline Oliveros, Yoko Ono, Orlan, Howardena Pindell, Yvonne Rainer, Faith Ringgold, Ketty La Rocca, Ulrike Rosenbach, Martha Rosler, Betye Saar, Miriam Schapiro, Carolee Schneemann, Cindy Sherman, Hannah Wilke
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; arts; arts visuels et médiatiques; corps; cours; discipline; femmes* artistes; har4600; histoire et politique; premier cycle; périodes historiques; thématiques

Self image: technology, representation, and the contemporary subject - Jones, Amelia (Routledge, 2006)
"Self/Image explores the ways in which contemporary artists have deployed new technologies of representation, from analogue photography to more recent artistic practices including digital imaging, performance, robotics, film and video installations, to explore and articulate shifting modes of subjectivity. This book is one of the first full-length studies to investigate the complex intersubjective relations among these diverse artistic practices." "Including over 100 illustrations from mainstream film to independent film, video art, performance and the visual arts, this important and original book provides an excellent companion to more general studies of contemporary art history, and media and cultural studies in the post-1960 period."–Résumé de l'éditeur.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; arts; arts visuels et médiatiques; corps; cours; discipline; film; har4600; histoire de l'art; performance; portrait; premier cycle; périodes historiques; représentation; thématiques; théorie de l'art

Radical gestures: feminism and performance art in North America - Wark, Jayne (McGill-Queen's University Press, 2006)
Wark brings together a wide range of artists, including Lisa Steele, Martha Rosler, Lynda Benglis, Gillian Collyer, Margaret Dragu, and Sylvie Tourangeau, and provides detailed readings and viewings of individual pieces, many of which have not been studied in detail before. She reassesses assumptions about the generational and thematic characteristics of feminist art, placing feminist performance within the wider context of minimalism, conceptualism, land art, and happenings
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; art contemporain; art féministe; arts; corps; cours; discipline; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire et politique; militance; performance; premier cycle; périodes historiques; régions géographiques; thématiques

Ouvrir la voie/x: le processus constitutif d'un sous-champ littéraire féministe au Québec, 1960-1990 - Boisclair, Isabelle (Éditions Nota bene, 2004)
À l’aube des années 1960, les femmes font massivement leur entrée dans le champ littéraire québécois. Comment expliquer ce phénomène ? Quel effet cela provoque-t-il dans le milieu du livre ? En examinant la condition des femmes en conjonction avec les configurations du champ littéraire et des différentes instances institutionnelles de 1960 à1990, Isabelle Boisclair décrit les différentes étapes du processus qui a permis l’intégration des femmes dans la vie littéraire. Se servant d’outils propres à l’histoire littéraire et à la sociologie de la littérature, scrutant tant la production, la diffusion, la réception que la consécration des écrits de femmes, cette étude se veut à la fois portrait et bilan. Les lecteurs et les lectrices trouveront dans cet ouvrage richement documenté aussi bien des faits souvent occultés par les manuels d’histoire que la révélation des réalisations des femmes dans le domaine littéraire, de leurs réussites tout autant que des obstacles idéologiques qu’elles ont rencontrés.
Section: 391 pages : illustrations ; 23 cm
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; amériques; arts; canada; cours; discipline; lit3495; premier cycle; périodes historiques; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

Analyse sociopoétique de la réception mitigée de deux œuvres de Clémence Desrochers : le monde aime mieux... et Mon dernier show - Gauthier, Mélissa (Université Laval, 2003)
https://central.bac-lac.gc.ca/.item?id=MQ90772&op=pdf&app=Library&oclc_number=1019512284
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; amérique du nord; amériques; arts; canada; chanson; discipline; femmes* artistes; monologue; mémoires/thèses; poésie; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sociologie; études littéraires

Corps, sexe et art: dimension symbolique - Pearl, Lydie (L'Harmattan, 2001)
Les années 60 marquent le début d'un art éphémère dans lequel l'objet d'art disparaît au profit d'une mise en scène du corps. Les Actionnistes viennois mêlent des corps féminins ou masculins dans la boue, du sang et des organes animaux etc. Comment ce qui peut paraître aberration ou perturbation de la personnalité est souvent une mise en scène microcosmique des idéologies ou des réalités politiques d'une époque : images d'une coupure Est/Ouest, de frontières infranchissables à l'époque de la guerre froide ou, au contraire, effacement des frontières au temps de la mondialisation avec des artistes de la Scène internationales
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; anthropologie; approches et analyses; art contemporain; arts; corps; cours; discipline; har4600; histoire de l'art; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; sciences humaines; sexualité; thématiques

Genders - Glover, David; Kaplan, Cora (Routledge, 2000)
"Gender" has, in recent years, become one of the busiest terms in literary and cultural theory, as well as being one of the most contested. David Glover and Cora Kaplan chart the main lines of contemporary debate surrounding gender in a guide which:* presents a history of the term, from the sexology of psychoanalysis of the 1960s to its current usage within the interdisciplinary field of gender studies* looks at the major perspectives on gender from second-wave feminist writers and critics* examines new work on masculinity in literary and cultural studies* assesses how the creation of new queer and gendered identities has impacted the study of literature* surveys empirical and theoretical work on readership and spectatorship, looking in detail at modes of fantasy, cultural consumption, reader response and fan cultures.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; amériques; antiféminisme; approches et analyses; cours; culture populaire; discipline; fem1000; littérature; masculinisme; premier cycle; périodes historiques; queer; ressource en ligne; régions géographiques; états-unis; études culturelles; études littéraires